Alcohol drinking behavior among people in the urban area of Udon Thani province - เคนศิลา อุมาพร; เคนศิลา จุฬารัตน์ (Journal of Ratchathani Innovative Health Sciences, 2019)
A survey of alcohol drinking behavior among people living in the urban area of Udon Thani province is a cross-sectional research survey. The research aims to study alcohol consumption behavior and the degree of risk among people residing in the Udon Thani province. Sample of the study consists of a simple random sampling of 102 people in Udon Thani. Data collection used a questionnaire survey and data was analyzed through percentage, mean and standard deviation. Result revealed that in the urban area of Udon Thani province the alcohol drinking behavior of the study sample was: 1) Low risk drinker 9.80 % 2) moderate risk drinker 31.37 % 3) excessive use 20.59 % and 4) Alcohol dependent 38.24 %. The study results show that the majority of alcohol consumption behavior among people in the urban area was alcohol dependency. The study concludes that this group should be referred to consult with a doctor for diagnosis and treatment planning.